South of Broad : a novel - Conroy, Pat (Dial Press, 2010)
After his brother's suicide, Leopold Bloom King struggles along with the rest of his family in Charleston, South Carolina, until he begins to gather an intimate circle of friends, whose ties endure for two decades until a final, unexpected test of friendship.